Perda visual conversiva em pós‐operatório de cirurgia de coluna: relato de caso - Bezerra, Dailson Mamede [UNESP]; Bezerra, Eglantine Mamede; Silva Junior, Antonio Jorge; Amorim, Marco Aurélio Soares; Miranda, Denismar Borges de (Elsevier, 2018)
Background and objective Patients undergoing spinal surgeries may develop postoperative visual loss. We present a case of total bilateral visual loss in a patient who, despite having clinical and surgical risk factors for organic lesion, evolved with visual disturbance due to conversion disorder. Case report A male patient, 39 years old, 71 kg, 1.72 m, ASA I, admitted to undergo fusion and discectomy at L4‐L5 and L5‐S1. Venoclysis, cardioscopy, oximetry, NIBP; induction with remifentanil, propofol and rocuronium; intubation with ETT (8.0 mm) followed by capnography and urinary catheterization for diuresis. Maintenance with full target‐controlled intravenous anesthesia. During fixation and laminectomy, the patient developed severe bleeding and hypovolemic shock. After 30 minutes, hemostasis and hemodynamic stability was achieved with infusion of norepinephrine, volume expansion, and blood products. In the ICU, the patient developed mental confusion, weakness in the limbs, and bilateral visual loss. It was not possible to identify clinical, laboratory or image findings of organic lesion. He evolved with episodes of anxiety, emotional lability, and language impairment; the hypothesis of conversion syndrome with visual component was raised after psychiatric evaluation. The patient had complete resolution of symptoms after visual education and introduction of low doses of antipsychotic, antidepressant, and benzodiazepine. Other symptoms also regressed, and the patient was discharged 12 days after surgery. After 60 days, the patient had no more symptoms. Conclusions Conversion disorders may have different signs and symptoms of non‐organic origin, including visual component. It is noteworthy that the occurrence of this type of visual dysfunction in the postoperative period of spinal surgery is a rare event and should be remembered as a differential diagnosis.
Postoperative visual loss due to conversion disorder after spine surgery: a case report
Keywords: Blindness; Conversion disorder; Decubitus ventral; General anesthesia; Laminectomy